Disturbance of Gut Bacteria and Metabolites Are Associated with Disease Severity and Predict Outcome of NMDAR Encephalitis: A Prospective Case–Control Study - Gong, Xue; Liu, Yue; Liu, Xu; Li, Aiqing; Guo, Kundian; Zhou, Dong; Hong, Zhen (Frontiers in Immunology, 2022)
Objective: To investigate the associations between intestinal flora, metabolites, cytokines and clinical severity in anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis, and further determine the predictive value of intestinal flora or metabolites in clinical prognosis. Methods: In this prospective observational cohort study of 58 NMDAR encephalitis patients and 49 healthy controls, fecal microbiota, metabolites, and cytokines were quantified and characterized by16S rRNA gene sequencing, liquid chromatography-mass spectrometry, luminex assay, respectively. Results: The composition of both the gut microbiota and metabolites changed significantly in critically-ill patients. We identified 8 metabolite modules (mainly characterized by fatty acid, glycerophosphoethanolamines, glycerophosphocholines) that were separately classified as being positively or negatively correlated with bacterial co-abundance group (CAG). These CAGs mainly composed of Bacteroides, Eubacterium_hallii_group, Anaerostipes, Ruminococcus, Butyricicoccus, Faecalibacterium, which substantially altered in patients. And these fecal and serum metabolic modules were further correlated with the serum cytokines, respectively. Additionally, the combination of clinical features, microbial marker (Granulicatella), and a panel of metabolic markers could further enhance the performance of prognosis discrimination significantly, which yield an AUC of 0.94 (95% CI, 0.75–0.97). Patients with low bacterial diversity are more likely to develop relapse than those with higher bacterial diversity [Log Rank p = 0.037, HR =2.74, 95%CI = (1.06,7.05)]. Interpretation: The associations between multi-omic data suggested that certain bacteria might affect the pathogenesis of NMDAR encephalitis by modulating metabolic pathways of the host and affecting the production of proinflammatory cytokines. Furthermore, the disturbance of fecal bacteria may predict the long-term outcome and relapse in NMDAR encephalitis.